Perceiving high social mindfulness during interpersonal interaction promotes cooperative behaviours. Issue 1 (23rd February 2018) - Dou, Kai; Wang, Yu‐Jie; Li, Jian‐Bin; Li, Jing‐Jing; Nie, Yan‐Gang
Abstract : Social mindfulness refers to individual's respect and protection of others' options in interpersonal interaction. The object‐choosing task is a traditional paradigm to assess social mindfulness. Individuals with high social mindfulness would choose the nonunique object so that others would have more options; on the contrary, individuals with low social mindfulness would choose the unique object, which limits others' choices. No prior study has examined whether perceiving people with different levels of social mindfulness affects one's cooperation. Based on this background, two experiments were conducted to address this question. In both experiments, a confederate participant's (Player A's) social mindfulness was manipulated by setting the frequency that Player A chose the unique and the nonunique objects. Then, participants were asked to interact with Player A in the public goods game (Experiment 1) or in the centipede game (Experiment 2). Convergent results showed that compared to those interacting with a socially unmindful person, participants interacting with a person perceived as socially mindful contributed more resources in the public goods game and chose to pass on more rounds in the centipede game. These findings suggest that perception of others' high social mindfulness enhances one's own cooperative behaviour.